The Problem Faced by Students Teacher Trainees During Teaching Practices at Secondary Schools. A Case Study of Political Student Teacher Trainees, Academic Year 2018 - 2019 - SIDAPHONE, Soulinthon; KHOTSAIGNOH, Saiphone; XANG, Yang; INTHAVONG, ViengArnousouk; PATHOUMVANH , Phanthamanath; SIVANHKHAM, Sengdeuan (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research was intended to investigation the problem during the instruction in secondary school by the trainee students from Faculty of Education, Souphanouvong University, and Academic year 2018-2020, Case Study: Political Science Trainees. The research aimed to investigate the processes three steps in instruction, including preparation, lecturing, and summarizing, have been conducted by teacher trainees. , the samples of research consist of 27 political science teacher trainees, 16 teacher from the secondary school and 80 students from 8 schools; these sample was select by purposive sampling. The instrument of this research consisted of 3 questionnaires with multiple choice; first questionnaire was adapted for the trainees teacher with total of 30 questions, the second was adapted for the teacher who Supervised the trainees with total of 25 questions; and the third questionnaire was adapted for the student with total of 25 perspective questions; The descriptive statistics were used to analyze the data which included the Mean and Standard Deviation (S.D) to find the the problems had been encountered during teaching practice. The research found that the instruction problems that were faced by the teacher trainees during the teaching practice in eight secondary schools were medium level by the mean of and the students’ attitude toward the teacher trainees' instruction was high-level by the mean of Although teacher trainees faced many challenges during their teaching practice due to their new experience in teaching, in reality they received very good care from the local people, and the students were also satisfied to a high level with the trainee’s instruction.